Heavy metals speciation in agricultural soils - Norzaimah, Jinggal (Universiti Malaysia Sarawak, UNIMAS, 2008)
Heavy metals in soils has been occurring naturally for million of years due to the natural weathering of the parent rocks and has increased due to other factors including application of agricultural materials such as fertilizer. Soil samples were collected from the pineapple farm in Kampung Meranek, Kota Samarahan. Soil characteristics namely pH, total organic matter and soil textural classes were determined. Total metals concentration of cadmium, chromium and mercury was determined. The extractability of the heavy metals with single extraction and sequential extraction between soils with fertilizer application and without fertilizer application was compared. The results showed that the highest total heavy metals concentration was chromium, followed by cadmium and mercury. The order of extractability of heavy metals in sampling sites was: Cd > Cr > Hg. The soils with fertilizer application showed higher heavy metals concentration compared to soil without fertilizer application. Statistical analysis showed no significant difference (P>0.05) for cadmium, chromium, and mercury concentrations in soils with fertilizer application and soils without fertilizer application. However, statistical analysis showed significant difference (P<0.05) for cadmium concentrations in different fractions in soils with fertilizer application. Chromium and mercury concentrations in different fractions showed significant difference in soils without fertilizer application but no significant difference in soils with fertilizer application. The sequential extraction procedure showed that all the heavy metals in both soils with fertilizer and without fertilizer application were dominant in the oxidizable fraction.